Sustentabilidade produtiva e efeito poupa-florestas na agricultura: Um comparativo internacional - Zenaide Rodrigues Ferreira; José Eustáquio Ribeiro Vieira Filho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– This study presents a comparative indicator of production sustainability in agriculture. Faced with the growing world demand for food and considering the centrality of the main producing and exporting countries of agricultural products in the world, it is important to identify the economies that are in fact committed to the sustainable aspect of their production. The indicator developed is based on the growth of total factor productivity (TFP), including greenhouse gas (GHG) emissions, a variable that directly reflects the sustainable trajectory of the agricultural sector. To complement the analysis, the indicator was also calculated based on the forest-saving effect. In this sense, for comparison, the ten main agro-exporting economies were selected, namely: United States, Holland, Brazil, Germany, France, Spain, China, Italy, Canada and Belgium. The results suggest that it is possible to simultaneously increase agricultural productivity, reduce polluting gas emissions and protect forests. Among the analyzed countries, Brazil led the standard indicators.
Keywords: Q10; Q40; Q50; 330; innovation; sustainable development; productivity; agriculture